Odyssean Motifs in the Middle Comedy: Witches, Monsters and Courtesans - Stuligrosz, Magdalena (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The purpose of this paper is to show how Middle Comedy authors re-work mythical motifs and characters borrowed from Homer’s epic poetry, inserting them into the various contexts of everyday life and imbuing them with new meaning. The analysis focuses on the fragments of plays by Anaxilas and Ephippus, which draw on the motif of animal transformation and of Odysseus’ encounter with Circe and mythical monsters.